A case of concomitant pulmonary tuberculosis and mucormycosis in an insulin-dependent diabetic patient. (August 2019) - O, Jiménez-Zarazúa; LN, Vélez-Ramírez; M, Alcocer-León; JD, Utrilla-Álvarez; MA, Martínez-Rivera; GA, Flores-Saldaña; JD, Mondragón
Abstract: Conditions, where the patient's immune system is compromised are the main risk factor for mucormycosis. Approximately 23% of the world's population is estimated to have a latent Mycobacterium tuberculosis infection and more than 10 million new cases were estimated in 2017. Pulmonary mucormycosis and tuberculosis co-infections are very rare. We present the case of a 56-year-old insulin-dependent diabetic patient with a pulmonary mucormycosis and tuberculosis co-infection. While the patient did not suffer from ketoacidosis, she had poor glycemic control. A chest X-ray and a computed tomography showed nodular and cavitary lesions in both lungs. The patient was diagnosed through a biopsy of the bronchial mucosa and an RT-PCR for M. tuberculosis from bronchoalveolar lavage. The patient was treated with the recommended 4-drug regimen for TB (i.e. isoniazid, rifampin, pyrazinamide, and ethambutol); concurrently, amphotericin B deoxycholate was administered to treat the mucormycosis infection. Thirty days after initial hospital admission the patient underwent a lobectomy on the right lung. The case described here is only the sixth case reported in the literature of concomitant pulmonary tuberculosis and mucormycosis and the third case associated with a TB and mucormycosis co-infection involving an uncontrolled DM patient to survive.